PENGGUNAAN OJEK SYARIAH SEBAGAI MODA TRANSPORTASI MUSLIMAH URBAN: MEREK ATAU RELIGIUSITAS? - Bafadhal, Aniesa Samira (Profit: Jurnal Adminsitrasi Bisnis, 2021)
The increasing need for travel in the local area of the house (staycation) such as shopping, culinary, health and education tours have encouraged the use of various modes of public transportation in urban communities. In the midst of these conditions, Muslimah's need for public transportation that meets the principles of sharia values and is safe from harassment and urban crime, OJESY is here as the first and only sharia motorcycle taxi for women in Indonesia. This study analyzes whether Muslimah consumers choose to use OJESY services because of the sharia brand offered by OJESY or because of consumer religiosity. The respondents of this study were 116 Muslim women using OJESY in Malang City, East Java. By using multiple regression the results of this study indicate that both the brand of sharia and religiosity show a significant and positive influence on customer decisions to use Islamic motorcycle taxi services, but religiosity is the main stimulus so spiritual-driven plays an important role in Muslimah decisions to use public transportation while maintaining the Islamic values it adheres to.